Hemp Seed Cake as a Novel Ingredient for Dog's Diet - Vastolo, Alessandro; Iliano, Sergio; Laperuta, Flaviana; Pennacchio, Saverio; Pompameo, Marina; Cutrignelli, Monica Isabella (Frontiers in Veterinary Science, 2021)
In the last few years, the popularity of industrial hemp and its products is increased. From a nutritional point of view hemp and its products are rich in protein, polyunsaturated fatty acids, vitamins, and useful minerals. Nowadays, European Commission authorizes the use of hempseed and hempseed oil co-products in animal nutrition. This study is aimed to evaluate the use of hempseed cake in dogs’ nutrition, comparing the effect of the supplementation of two lipid sources: swine tallow (T-diet) and hempseed cake (H-diet). A double-blind nutritional trial was performed at a municipal kennel located in Naples. Eight crossbreed neutered dogs recognized in good health were recruited and divided into two homogeneous groups (T- vs. H-group). Both diets were analyzed for chemical composition and fatty acids profile. Blood count and biochemical profile were evaluated at recruitment (T0) and the end of the trial (T30). Oleic, palmitic, and stearic acids were the most representative fatty acids in both diets; however, H-diet contains more than double the concentration of linoleic and α-linoleic acids compared to T-diet (p<0.01). The H-diet has shown significantly (p<0.01) higher peroxidation index as the only negative aspect, that could compromise its shelf-life. After 30 days of the administration, H-group has shown a significant (p<0.01 and p<0.05) reduction of liver and renal markers (AST, ALT, and creatinine) and cholesterol, due to the healthier fatty acids profile. Hempseed cake seems a suggestable source of polyunsaturated fatty acids for pet-food industries considering these preliminary results.